2016
DOI: 10.6017/ihe.2016.86.9365
|View full text |Cite
|
Sign up to set email alerts
|

Managing Markets and Massification of Higher Education in India

Abstract: The market friendly reforms of the 1990s encouraged proliferation of private higher education institutions and massification of the sector. Massification is accompanied by persisting inequalities, declining quality and poses challenges to effectively manage the system.  This paper argues for a more regulated growth of private higher education and targeted public investments in favour of disadvantaged groups and deprived regions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 0 publications
0
20
0
2
Order By: Relevance
“…Hornsby and Osman (2014) describing massification as a phenomenon that results in large class teaching in higher education, considered it as "a problem in promoting student learning, quality education, and consequently as a challenge to socio-economic development" since large class pedagogy generally correlates with low student performance (Hornsby & Osman, 2014). Varghese (2015), exploring the massification of higher education in India, found that the challenges posed by massification are considerable in higher education institutions. Such challenges include "concerns for ensuring equity, improving quality, mobilizing funding, managing and regulating the system", which requires the role of the State to change "from financing and managing institutions to developing a framework for regulating the system to ensure equity in access and quality in outcomes" (Varghese, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Hornsby and Osman (2014) describing massification as a phenomenon that results in large class teaching in higher education, considered it as "a problem in promoting student learning, quality education, and consequently as a challenge to socio-economic development" since large class pedagogy generally correlates with low student performance (Hornsby & Osman, 2014). Varghese (2015), exploring the massification of higher education in India, found that the challenges posed by massification are considerable in higher education institutions. Such challenges include "concerns for ensuring equity, improving quality, mobilizing funding, managing and regulating the system", which requires the role of the State to change "from financing and managing institutions to developing a framework for regulating the system to ensure equity in access and quality in outcomes" (Varghese, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Varghese (2015), exploring the massification of higher education in India, found that the challenges posed by massification are considerable in higher education institutions. Such challenges include "concerns for ensuring equity, improving quality, mobilizing funding, managing and regulating the system", which requires the role of the State to change "from financing and managing institutions to developing a framework for regulating the system to ensure equity in access and quality in outcomes" (Varghese, 2015). Mok and Jiang (2016), exploring issues related to the massification of Chinese higher education, observe that massification may affect the competitiveness of university graduates in the job market since it can lead to poor quality education and hence to educationjob mismatch (Mok & Jiang, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…25 Given the high demand for higher education and the political aspiration to increase access, the use of cost-recovery policies has become standard practice. Household spending on higher education has increased markedly in India, Pakistan, and Nepal (Varghese 2015). Another major factor behind increased privatization may have been the benefits accruing to politicians who themselves undertook to open private institutions (Kapur and Mehta 2004).…”
Section: The Political Economy Of Privatization: Private Colleges Arementioning
confidence: 99%
“…India has experienced a rapid increase in the participation at the HE level, supported by the central and state governments along with private parties through opening up of publicly funded educational institutions, opening up of new centres or departments in existing educational institutions, scholarship programmesboth merit-based and need-based-and educational loans (Varghese, 2015). However, in spite of this expansion, a large proportion of participation in HE is shared by students from higher socio-economic backgrounds.…”
Section: Theoretical Premise and Evidence From The Literaturementioning
confidence: 99%